2015
DOI: 10.1038/gim.2015.6
|View full text |Cite|
|
Sign up to set email alerts
|

CRIM-negative infantile Pompe disease: characterization of immune responses in patients treated with ERT monotherapy

Abstract: Purpose Enzyme replacement therapy (ERT) with recombinant human GAA (rhGAA) prolongs survival in infantile Pompe disease (IPD). However, the majority of cross reactive immunologic material (CRIM)-negative (CN) patients have immune responses with significant clinical decline despite continued ERT. We aimed to characterize immune responses in CN IPD patients receiving ERT monotherapy. Methods A chart review identified 20 CN IPD patients treated with ERT monotherapy for ≥6 months. Patients were stratified by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 21 publications
1
73
0
2
Order By: Relevance
“…Additional factors, such as the age and the stage of disease at ERT initiation, also contribute to clinical outcome [45,46]. A recent study that focused only on the treatment outcomes of CRIM-negative patients also suggested that the majority but not all of CRIM-negative patients mounted a significant immune response [47]. The ones that did not develop a significant immune response had unique genotypes, either a frameshift or a splice site mutation in GAA [47].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional factors, such as the age and the stage of disease at ERT initiation, also contribute to clinical outcome [45,46]. A recent study that focused only on the treatment outcomes of CRIM-negative patients also suggested that the majority but not all of CRIM-negative patients mounted a significant immune response [47]. The ones that did not develop a significant immune response had unique genotypes, either a frameshift or a splice site mutation in GAA [47].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A recent study that focused only on the treatment outcomes of CRIM-negative patients also suggested that the majority but not all of CRIM-negative patients mounted a significant immune response [47]. The ones that did not develop a significant immune response had unique genotypes, either a frameshift or a splice site mutation in GAA [47]. Thus, we should consider CRIM status also as a continuum, from CRIM-negative at one end to strongly CRIMpositive at the other end of the spectrum.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…3 Herbert and colleagues may have missed the fact that only a few adult patients develop high sustained antibodies, which is in contrast to the situation in classic infantile patients. A recent study by Masat et al 4 on behalf of the French Pompe Registry Study Group also concluded that antibodies are not a major concern in adults with Pompe disease. 4 …”
Section: Response To De Vries Et Almentioning
confidence: 99%
“…A recent study by Masat et al 4 on behalf of the French Pompe Registry Study Group also concluded that antibodies are not a major concern in adults with Pompe disease. 4 …”
Section: Response To De Vries Et Almentioning
confidence: 99%
See 1 more Smart Citation